Synthesis of agricultural land system change in China over the past 40 years - Sun, Z.; You, L.; Müller, D. (Informa UK Limited, 2018)
Understanding the patterns, processes, and causes of land use changes remains the core task and challenge of land system science (Rounsevell et al., 2012; Turner, Lambin, & Reenberg, 2007; Verburg, Erb, Mertz, & Espindola, 2013). While area changes that include agricultural expansion, urbanization, and deforestation have long attracted the most attention in land system science, relatively little research has been conducted regarding the more subtle changes within these broad land use categories, such as modifications of agricultural intensity (Kuemmerle et al., 2013). The spatial patterns and configuration of land use, changes in land tenure, and land use intensification all have profound implications on food security, natural resources, and the environment (Deng, Huang, Rozelle, & Uchida, 2006; Haines-Young, 2009). For example, while the spatial concentration of crops and intensification of agriculture may have positive effects on the agricultural productivity necessary to meet increasing food demand, they also have caused the loss of biodiversity, depletion of water resources, soil exhaustion, surface and groundwater pollution, and increased carbon emissions (Kleijn et al., 2008; Matson, Parton, Power, & Swift, 1997; Searchinger et al., 2008; Tilman, Balzer, Hill, & Befort, 2011). Representing one of the core challenges of sustainable development is the persistent tension between increasing agricultural productivity to feed, clothe, house, and fuel the world’s growing population in the near term and ensuring environmental quality and resource sustainability to support humanity’s existence in the long term (Swinton, Lupi, Robertson, & Hamilton, 2007; Zhang, Ricketts, Kremen, Carney, & Swinton, 2007). These opposing pressures point to the need for greater evidence-based discourse on competing uses of land, spatial patterns of land use, and their impact on food availability and well-being.